2018
DOI: 10.1007/s00482-018-0290-x
|View full text |Cite
|
Sign up to set email alerts
|

Pain in older adults with dementia

Abstract: Our findings suggest that pain education is required across all countries surveyed. This should include a focus on guidelines and standards for assessment and subsequent management of pain. Findings suggest that clinical staff find interpreting facial expressions in relation to pain more difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 37 publications
(33 reference statements)
2
17
0
Order By: Relevance
“…Therefore, the current study confirmed many findings from the original E.U. survey ( 22 ). The majority of participants did not use national/international standards, guidelines, or local policies or were unsure if their institutions had any pain management guidelines (E.U.…”
Section: Discussion/conclusionsupporting
confidence: 89%
See 3 more Smart Citations
“…Therefore, the current study confirmed many findings from the original E.U. survey ( 22 ). The majority of participants did not use national/international standards, guidelines, or local policies or were unsure if their institutions had any pain management guidelines (E.U.…”
Section: Discussion/conclusionsupporting
confidence: 89%
“…This survey was conducted across the central European participating countries, including questions about participants' knowledge and use of existing pain assessment guidelines, the usage of existing pain assessment (observational tools) and the experience health care professionals have of implementing the tools. Recently, this survey results in central-north Europe have been reported ( 22 ), and here we present the results from southern Europe (Spain). The preliminary analysis on one of the “open questions” regarding the professional concerns on problems experienced in Spain and solutions for its improvement was presented for discussion with the scientific community of the International Psychogeriatric Association in our last IPA International Congress ( 23 ).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…30,63 A recent European survey on pain assessment in older adults with dementia provides further insights into perceived challenges in pain management for persons with severe cognitive impairment. 64 Health-care professionals stated that behavioral assessment instruments are often too difficult to complete due to the lack of objectivity. The main criticism was the high subjectivity in the evaluation of pain items (ie behavioral characteristics) and the difficulty to interpret resulting scores of the measures currently available-the authors conclude the high-priority importance to improve the usefulness of proxy pain assessment instruments.…”
Section: Discussionmentioning
confidence: 99%